2022
DOI: 10.3389/fsoil.2022.1028328
|View full text |Cite
|
Sign up to set email alerts
|

Using phosphate amendments to reduce bioaccessible Pb in contaminated soils: A meta-analysis

Abstract: Measuring the reduction of in vitro bioaccessible (IVBA) Pb from the addition of phosphate amendments has been researched for more than 20 years. A range of effects have been observed from increases in IVBA Pb to almost 100% reduction. This study determined the mean change in IVBA Pb as a fraction of total Pb (AC) and relative to the IVBA Pb of the control soil (RC) with a random effects meta-analysis. Forty-four studies that investigated the ability of inorganic phosphate amendments to reduce IVBA Pb were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
1
0
1
Order By: Relevance
“…Soil amendment strategies presented in Figs. 1 and A recent meta-analysis review of phosphate amendment studies [51] identified that soluble amendments such as PA showed higher immobilization efficacy than insoluble amendments such as RP. TERs may also vary due to differences in application rates (0.5-10% w/w), P:Pb molar ratios (1:1-5:1), the presence of other soil constituents (e.g., Ca and Zn), which may interact with phosphate, contamination source and the initial concentration of Pb in soils (i.e., highly contaminated mine impacted soils vs. low/ mild elevation as in most urban soils).…”
Section: Impact Of Soil Amendments On Pb and As Relative Bioavailabilitymentioning
confidence: 99%
“…Soil amendment strategies presented in Figs. 1 and A recent meta-analysis review of phosphate amendment studies [51] identified that soluble amendments such as PA showed higher immobilization efficacy than insoluble amendments such as RP. TERs may also vary due to differences in application rates (0.5-10% w/w), P:Pb molar ratios (1:1-5:1), the presence of other soil constituents (e.g., Ca and Zn), which may interact with phosphate, contamination source and the initial concentration of Pb in soils (i.e., highly contaminated mine impacted soils vs. low/ mild elevation as in most urban soils).…”
Section: Impact Of Soil Amendments On Pb and As Relative Bioavailabilitymentioning
confidence: 99%
“…. Para diferenciar entre medições in vivo e in vitro, os resultados in vitro são referidos como bioacessíveis(MAYER;BASTA;SCHECKEL, 2022). A bioacessibilidade é uma medida in vitro (IVBA, do inglês in vitro bioacessibility) da solubilidade fisiológica da substância química(US EPA, 2017).…”
unclassified